Analisis Peran Kesenian Reog Kendang Sebagai Upaya Meningkatkan Nilai Moral Pelajar di Wilayah Kabupaten Tulungagung - Sibit Werda Anugrah Kinasen; Nadya Khusna Alfiany; Anggoro Putranto (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2023)
The original Reog Kendang art comes from Tulungagung Regency which was formed based on a folk dance composition created in 1978, this dance presents the process of troop soldiers from the Kedhiri Kingdom who followed Queen Kilisuci's procession to Mount Kelud to witness the conditions that queen Kilisuci gave to Jathasura. The people of Tulungagung know this art as a simple entertainment that can be performed by six dancers simultaneously dancing and beating the dhodhog drums. Instilling moral values in a student can be done through art, especially the Reog Kendang art. This art teaches children to have courtesy, cooperation, responsibility and so on in order to create and present beautiful art.